Dampak Ketidaklengkapan Rekam Medis Rawat Inap Kasus Covid-19 Terhadap Pelayanan di Rumah Sakit Condong Catur Yogyakarta - Paskalia Gabrielsa Dehoni; Kori Puspita Ningsih (Universitas Ahmad Dahlan, 2021)
A well-written and complete medical record have many uses, including aspects of administration, legal, finance, research, education and documentation (ALFRED). Therefore, incomplete medical records will have an impact on hospital services. To find out the benefits of medical records from users in RSCC and to know the type of medical record form to claim Covid-19 patients at RSCC. Also, to find out the impact of incomplete inpatient medical records for Covid-19 cases from the aspects of Administration, Legal, Finance, Research, Education, Documentation (ALFRED) at RSCC. This study used a qualitative descriptive method with a case study design. The informants in this study are 11 people consisting of 1 medical record officer, 1 distribution officer, 1 covid-19 claim officer, 1 claim verification doctor, 1 head of medical services, 1 head of medical support, 1 head of ICU officer, 1 head of inpatient care officer, 2 heads of ward officers and 1 head of nursing. The object of this study used 8 inpatient medical records of Covid-19 patients in the period January-March 2021 at RSCC. In addition, the head of RSCC medical record carried out data validation as triangulation. The benefits of medical records for health care workers at the RSCC are knowing the activities of health care providers in treating patients, BPJS/insurance claims and predicting hospital income, as a source of data for research, learning materials about service activities in hospitals, to know about patient medical history and hospital reports. In claiming Covid-19 patients, the RSCC uses medical resumes, Covid-19 screening, laboratory results, isolation certificates, CPPT sheets, medical prescriptions, and inpatient approval sheets. However, the incompleteness of medical records from the administrative aspect causes delays in the administrative process, the financial aspect causes claims to be disputed, and the documentation aspect causes delays in the making of hospital reports. Incompleteness of medical records at RSCC have impacts on administrative aspects, financial aspects, and documentation aspects.